Global Macro-Financial Cycles and Spillovers - Jongrim Ha; M. Ayhan Kose; Christopher Otrok; Eswar Prasad (Institute of Labor Economics (IZA), 2020)
We develop a new dynamic factor model that allows us to jointly characterize global macroeconomic and financial cycles and the spillovers between them. The model decomposes macroeconomic cycles into the part driven by global and country-specific macro factors and the part driven by spillovers from financial variables. We consider cycles in macroeconomic aggregates (output, consumption, and investment) and financial variables (equity and house prices, and interest rates). We find that the global macro factor plays a major role in explaining G-7 business cycles, but there are also spillovers from equity and house price shocks onto macroeconomic aggregates. These spillovers operate mainly through the global macro factor rather than the country-specific macro factors (i.e., these spillovers affect business cycles in all G-7 economies) and are stronger in the period leading up to and following the global financial crisis. We find little evidence of spillovers from macroeconomic cycles to financial cycles.
Keywords: E32; F4; C32; C1; 330; global business cycles; global financial cycles; common shocks; international spillovers; dynamic factor models